PENGARUH MUSIM TERHADAP PLANKTON DI PERAIRAN RIAU KEPULAUAN DAN SEKITARNYA - Thoha, Hikmah (UI Scholars Hub, 2003)
Seasonal influenzed on plankton of the waters around Riau islands. The observation was conducted during April - May 2002. This study was done in relation with observation on environment quality of the waters around Riau Islands. The parameter observed were focus on the plankton communities for tweentyfives points of stations which were grouped into two zone based on the distance of the each station. Plankton abundance varied with location groups from 50- 90 % respectively. Community structure was dominated by the group of diatoms such as Chaetoceros, Dytilum, Nitzschia, Thalassionema, Thalassiothrix and the genus Ceratium (the group of Dinoflagellata). Community structure of zooplankton was dominated by the group of Copepods (45 – 90 %) and Polychaeta, Chaetognata, Bivalvia, Gastropods and Oikopleura (more than 90 %). The results describe the relationship between the water environmental condition and variation of plankton condition